2014
DOI: 10.1111/cas.12351
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: MicroRNA‐16 inhibits glioma cell growth and invasion through suppression of BCL2 and the nuclear factor‐κB1/MMP9 signaling pathway

Abstract: Recent studies have identified a class of small non-coding RNA molecules, named microRNA (miRNA), that is dysregulated in malignant brain glioblastoma. Substantial data have indicated that miRNA-16 (miR-16) plays a significant role in tumors of various origins. This miRNA has been linked to various aspects of carcinogenesis, including cell apoptosis and migration. However, the molecular functions of miR-16 in gliomagenesis are largely unknown. We have shown that the expression of miR-16 in human brain glioma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
108
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 38 publications
9
108
1
Order By: Relevance
“…At present, many inhibitors and microRNAs targeting Bcl-2 have been studied. miR-16 can inhibit glioma cell growth and invasion through the suppression of Bcl-2 (27). miR-18, a tumor-suppressive miRNA directly targeting Bcl-2, participated in suppression of cell proliferation and survival in nasopharyngeal carcinoma (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many inhibitors and microRNAs targeting Bcl-2 have been studied. miR-16 can inhibit glioma cell growth and invasion through the suppression of Bcl-2 (27). miR-18, a tumor-suppressive miRNA directly targeting Bcl-2, participated in suppression of cell proliferation and survival in nasopharyngeal carcinoma (29).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in the Bcl-2 gene may be associated with the risk of endometrial cancer in Chinese women (26). Some studies found that inhibitors and microRNA targeting Bcl-2 had effect on treatment of gliomas (27), myeloma (28), nasopharyngeal carcinoma (29), esophageal squamous cell carcinoma (30), aclcoholic liver disease (31), colorectal (32), gastric cancer (33) and melanoma (34).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-21 acts as an antiapoptotic factor in GBM by targeting the p53 network (8 -10); miR-10b is involved in the cell cycle and programmed cell death via regulating the expression of Bim, TFAP2C, p16, and p21 (11); miR-218 inhibits cell migration, invasion, proliferation, and stem-like qualities by targeting Bmi1 (12); miR-195 negatively regulates the proliferation of glioma cells by down-regulating the expression of cyclin D1 and cyclin E1 (13); miR-137 inhibits the growth of glioma cells by directly targeting Rac1 (14); and miR-16 functions as a tumor suppressor gene in glioma growth and invasiveness via the inhibition of BCL2 and the NF-KB1/MMP-9 signaling pathway (15). All of these miRNAs play important roles in the development of the malignant GBM phenotype.…”
mentioning
confidence: 99%
“…BCL2 contributes a crucial role in cell death, apoptosis, migration and invasion (3,9,23,24). Previous studies have reported that BCL2 is involved in the pathogenesis of laryngeal cancer (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%